The assessment of the process of drawing a cylindrical workpiece without pressing with alternating strain of the workpiece flange - Arhat Roman; Shchetynin Viktor; Puzyr Ruslan; Savelov Dmitry; Haikova Tetiana (E3S Web of Conferences, 2021)
The development of a method for drawing cylindrical parts without pressing the workpiece flange, which allows reducing the cost of production due to the use of dies without a fit ring and single-acting presses. The performed research revealed that this method results in obtaining cylindrical parts with drawing ratios typical for pressing drawing. In this case, the different thickness of the finished product is several times less compared with the same type of semi-finished products obtained by drawing with a fit ring. Steel, aluminum and copper workpieces were researched. The best results were shown by more plastic materials. This method is not applicable for materials with the less than 0.25 mm thickness.